Structure-guided design of a bivalent SARS-CoV-2 mRNA vaccine with NTD stabilizing mutations enhances broad immunity - Yeo, Jinah; Yun, Mi-ran; Kim, Seo-Yeon; Seok, Jong-Hyun; Jeon, Ji Hyang; Lee, Taeyoung; Kim, Jeonghun; Kim, Kisoon; Park, Man-Seong; Kim, Dokeun; Kim, You-Jin (Frontiers in Immunology, 2026)
SARS-CoV-2 evolution, particularly the emergence of Omicron variants, has challenged vaccine efficacy, necessitating antigens with broad and variant-specific protection. To design mRNA vaccine antigens with broad-spectrum immunity and enhanced stability, we developed two spike antigens using in silico optimization: Css_dsg S, the ancestral strain–Delta variant consensus with stabilizing mutations, and Omi_dsg S, an Omicron-adapted design. Computational analysis identified two critical N-terminal domain stabilization sites consistently enhancing protein expression across variants, suggesting their potential as universal stabilizing elements. Css_dsg S elicited robust IFN-γ T cell responses and significantly elevated neutralizing antibody titers against variants in BALB/c mice. Omi_dsg S induced strong immune responses in vivo. A bivalent mRNA vaccine combining both antigens elicited superior neutralizing antibody responses and conferred enhanced protection against BN.1 and BA.5 challenges in K18-hACE2 mice. These findings support computationally optimized spike antigens, particularly the bivalent formulation, as a promising strategy for next-generation vaccines against SARS-CoV-2 variants.